Dynamic Response of Self-Supported Power Transmission Tower Subjected to Wind Action - Hamzah, Nur Hamizah; Usman, Fathoni; Mat Yatim, Mohd Yazee (International Journal of Engineering and Technology, 2018)
A power transmission tower carries electrical transmission conductor at adequate distance from the ground. It must withstand all nature’s forces besides its self-weight. In structural analysis, natural frequency, mode shape and damping ratio are used to define the structural dynamic properties which relate to the basic structural features. This paper described the dynamic analysis including the modal and the time history analysis on each segment of the self-supported transmission tower to understand its dynamic responses subjected to wind action. The factors such as different height above ground, a different value of wind speed and different wind angle of attack were included in this study to see the influence of those factors towards dynamic response of the structure. The contribution of the wind towards the displacement of the structure is determined in this study by comparing the result obtained in a linear static analysis which considered the load combination without and with the presence of wind action. It was found that displacement using dynamic analysis is bigger than static linear analysis. The result illustrates that the studied factors gave a significant effect on the dynamic response of the structure and the findings indicate that dynamic analysis is vital in structural design.